Urban architecture and human behavior: An approach to the theories of Henri Lefebvre and others authors to analyze the urbanization process in Suba, Bogotá - González Rojas, Nicolás (Universidad del Rosario, 2013)
There has been scientific research focusing specifically on the process of urbanization in Suba, a suburb located in Bogota, Colombia. The prime objective of this research was to investigate the ways in which social relations are interwoven among the first inhabitants who have lived through this urbanization process with the current population. This data was obtained utilizing a theoretical and empirical approach to explain how this phenomenon could have social impact, where Suba has a social duality; a small population linked to it’s past, meshed with it’s large rural population so accustom to city life.